Soil and water assessment tool : (Grassland, Soil and Water Research Laboratory, 2004)
The document is a graphical user interface for the SWAT (Soil and Water Assessment Tool) model (Arnoil et al. 1998). SWAT is a river basin or watershed, scale model developed to predict the impact of land management practices on water, sediment and agricultural chemical yields in large, complex watersheds with varying soils, land use, and management conditions over long periods of time.